2020
DOI: 10.1016/j.jsps.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Galenia africana plant extract exhibits cytotoxicity in breast cancer cells by inducing multiple programmed cell death pathways

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(45 reference statements)
2
12
0
Order By: Relevance
“…In agreement with the present finding, various studies reported plant extracts with similar effects in various cancer cell lines, including MCF-7 and MDA-MB-231 cell lines [ 37 , 38 ]. This finding is consistent with the report that an extract from Galenia africana inhibited the cell migration by downregulating the mesenchymal markers, vimentin and β-catenin, and upregulating E-cadherin, a well characterized epithelial marker [ 39 ]. Since cell migration involves the transition of epithelial cells into motile mesenchymal cells [ 40 ] and thus promotes CSC migration, contributing to the reconstitution of metastatic cancer at distant sites [ 41 , 42 ], the present finding implicates that the bioactive fractions may contribute to reducing the metastatic burden of breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the present finding, various studies reported plant extracts with similar effects in various cancer cell lines, including MCF-7 and MDA-MB-231 cell lines [ 37 , 38 ]. This finding is consistent with the report that an extract from Galenia africana inhibited the cell migration by downregulating the mesenchymal markers, vimentin and β-catenin, and upregulating E-cadherin, a well characterized epithelial marker [ 39 ]. Since cell migration involves the transition of epithelial cells into motile mesenchymal cells [ 40 ] and thus promotes CSC migration, contributing to the reconstitution of metastatic cancer at distant sites [ 41 , 42 ], the present finding implicates that the bioactive fractions may contribute to reducing the metastatic burden of breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…This shows that the cell viability of A375 cells was affected in a time and dose-dependent manner. A similar study also reported that G. africana could reduce cell viability of malignant breast cancer cell lines MCF-7 and MDA-MB-231 (IC 50 values of 114.0 and 130.5 µg/mL) in a dose-dependent manner, respectively [34]. This further substantiating the extract's anti-proliferative effects.…”
Section: Discussionsupporting
confidence: 68%
“…This suggests that the extract is not harmful to healthy cells at concentrations between 100-200 µg/mL after 24, 48 and 72 h of exposure. A similar study has also reported that G. africana was less effective in reducing the cell viability of non-malignant fibroblast and breast epithelial (IC 50 values of 185.5 and 159.8 µg/mL), respectively [34]. While another study showed that G. africana was non-toxic as it did not induce a hypersensitivity response or cause any dermal sensitization to the epidermis [30].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The ability of cancer cells to migrate from the primary site and form tumors at the distal sites is the major cause of morbidity in cancer patients 36 . Therefore, we next assessed the anti‐migratory effect of MBE using the wound‐healing assay.…”
Section: Resultsmentioning
confidence: 99%